Carbon and nitrogen stocks and N2O emission under diferent land use in Atlantic Forest biome - Coutinho, Rodolfo Pellegrini; Urquiaga, Segundo; Boddey, Robert Michael; Alves, Bruno José Rodrigues; Torres, Anatoly Queiroz Abreu; Jantalia, Claudia Pozzi (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the impact on soil organic matter dynamics and N2O emission of the substitution of pasture areas by eucaliptus reforestation and secondary forest. The evaluated areas are localized in Cruzeiro municipality, São Paulo state, Brazil. The areas presented common soil usage history, and were used, at first, as pasture. Since 1973, part of the area was reserved for regeneration of the secondary forest, another part was planted with eucalyptus, and the remaining was kept as pasture. To quantify the stocks of C, N and in soil and the 13C isotopic abundance in soil organic matter (SOM), samples from these areas were collected until 1-m depth, using three replicates. The emission of N2O was evaluated with static chambers for one year. The three areas did not show significant differences on C and N stocks of the secondary forest and eucalyptus areas, in comparison to the pasture one. Secondary forest and eucalyptus has greater carbon contribution to SOM. Secondary forest and eucalyptus have highest annual losses of N, as N2O.